ANALISIS PENGARUH TINGKAT INFLASI TERHADAP PENGHIMPUNAN ZIS BAZNAS TAHUN 2005 - 2015: PENGARUH TINGKAT INFLASI TERHADAP PENGHIMPUNAN ZIS BAZNAS - Muhammad Zeinny, Muhammad Zeinny Hasbunallah Sasmita (LP2M IBK Nitro, 2025)
This study aims to analyze the effect of inflation levels on the collection of Zakat, Infaq, and Shadaqah (ZIS) by the National Amil Zakat Agency (BAZNAS) in Indonesia from 2005 to 2015. ZIS is a key source of funds for poverty alleviation, and understanding the factors that influence its collection is crucial for improving the efficiency of zakat management. The research employs a quantitative approach, utilizing time-series data of BAZNAS ZIS collections and inflation rates during the specified period. Using regression analysis, the study investigates the correlation between inflation rates and the fluctuations in ZIS collections, controlling for other economic factors such as GDP growth and unemployment. The findings suggest a significant negative relationship between inflation and ZIS collection, indicating that rising inflation decreases public contributions to zakat. This result underscores the need for strategic adjustments in zakat collection mechanisms during economic instability to ensure sustained financial support for the poor. The study provides valuable insights for policymakers and BAZNAS in optimizing ZIS collection amidst economic challenges